Undoing privilege : unearned advantage in a divided world - Pease, Bob (Zed Books ; Distributed exclusively in the USA by Palgrave Macmillan, 2010)
"̀This is a scholarly, well-written book that offers a refreshingly new viewpoint about challenging and confronting an unequal and unjust world order. The author's transparent sincerity, humility and acute awareness about one's privileged position are embedded throughout the narrative.' Dr Ravindra RP, Narsee Monjee Institute of Management Studies" "Ùndoing Privilege confronts major taken-for-granted dimensions of privilege: Western, class, gender, race, sexual, embodied. It also outlines ways undo all this, in theory, practice and indeed activism - a huge taks that makes for a very important book, written with brevity and humility.' Professor Jeff Hearn, Linkoping University, author of the Gender of Oppression" "̀This landmark work takes our understanding of privilege to a new level.' Abby Ferber, director, The Matrix Center for the Advancement of Social Equity and Inclusion" "For every group that is oppressed, another group is privileged. In Undoing Privilege, Bob Pease argues that privilege, as the other side of oppression, has received insufficient attention in both critical theories and in the practices of social change. As a result, dominant groups have been allowed to reinforce their dominance." "Undoing Privilege explores the main sites of privilege, from Western dominance, class elitism, and white and patriarchal privilege to the less-examined sites of heterosexual and able-bodied privilege. Pease points out that while the vast majority of people may be oppressed on one level, many are also privileged on another. He also demonstrates how members of privileged groups can engage critically with their own dominant position, and explores the potential and limitations of them becoming allies against oppression and their own unearned privilege." "This is an essential book for all who are concerned about developing theories and practices for a socially just world."--Jacket.